The Complicated Partisan Effects of State Election Laws. (September 2017) - Burden, Barry C.; Canon, David T.; Mayer, Kenneth R.; Moynihan, Donald P.
Conventional political wisdom holds that policies that make voting easier will increase turnout and ultimately benefit Democratic candidates. We challenge this assumption, questioning the ability of party strategists to predict which changes to election law will advantage them. Drawing on previous research, we theorize that voting laws affect who votes in diverse ways depending on the specific ways that they reduce the costs of participating. We assemble datasets of county-level vote returns in the 2004, 2008, and 2012 presidential elections and model these outcomes as a function of early voting and registration laws, using both cross-sectional regression and difference-in-difference models. Unlike Election Day registration, and contrary to conventional wisdom, the results show that early voting generally helps Republicans. We conclude with implications for partisan manipulation of election laws.